2013
DOI: 10.2967/jnumed.112.112219
|View full text |Cite
|
Sign up to set email alerts
|

Multisoftware Reproducibility Study of Stress and Rest Myocardial Blood Flow Assessed with 3D Dynamic PET/CT and a 1-Tissue-Compartment Model of 82Rb Kinetics

Abstract: Routine quantification of myocardial blood flow (MBF) requires robust and reproducible processing of dynamic image series. The goal of this study was to evaluate the reproducibility of 3 highly automated software programs commonly used for absolute MBF and flow reserve (stress/rest MBF) assessment with 82 Rb PET imaging. Methods: Dynamic rest and stress 82 Rb PET scans were selected in 30 sequential patient studies performed at 3 separate institutions using 3 different 3-dimensional PET/CT scanners. All 90 sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 19 publications
2
69
2
1
Order By: Relevance
“…Non-gated images were presented in the horizontal and vertical long axis and in the short axis, and displayed in a polar map format divided into 17 segments, as suggested by the American Heart Association [13], and normalised to peak myocardial activity (100%) [14]. Myocardial blood flow was calculated automatically using the Siemens Syngo MBF 2.3 (Siemens Medical Solutions, Malvern, PA, USA) with one-compartment tracer kinetic models for 82 Rb, including regional uptake and clearance variables, blood to myocardium spill-over and partial volume corrections [15], and the extraction curve from Lortie et al [16]. Maximal hyperaemia was induced with adenosine infused at 140 μg kg −1 min −1 for 6 min.…”
Section: Methodsmentioning
confidence: 99%
“…Non-gated images were presented in the horizontal and vertical long axis and in the short axis, and displayed in a polar map format divided into 17 segments, as suggested by the American Heart Association [13], and normalised to peak myocardial activity (100%) [14]. Myocardial blood flow was calculated automatically using the Siemens Syngo MBF 2.3 (Siemens Medical Solutions, Malvern, PA, USA) with one-compartment tracer kinetic models for 82 Rb, including regional uptake and clearance variables, blood to myocardium spill-over and partial volume corrections [15], and the extraction curve from Lortie et al [16]. Maximal hyperaemia was induced with adenosine infused at 140 μg kg −1 min −1 for 6 min.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence of good agreement between software packages for blood flow quantification with 82 Rb [17] and 13 N-ammonia [18] studies and it has been stated that reconstruction using a wide range of software, under the assumption of a 1-tissue compartment mode, has sufficient agreement to be used interchangeably. Nevertheless, it has also been demonstrated that agreement is not optimal between estimations derived from different kinetic models [19].…”
Section: Dedicated Softwarementioning
confidence: 99%
“…6 Similarly, when point spread function modeling and time-of-flight reconstructions are compared to standard PET reconstructions, CFR results are consistent, but marked variations in rest and stress MBF have been reported. 7 Fortunately, when the same data set is analyzed with different automated software programs, MBF results are comparable, provided the analysis is performed with the same one-compartment model of 82 Rb kinetics. 8 Regarding variations in data acquisition, the vasodilator and timing of radionuclide injection both influence maximal hyperemia.…”
mentioning
confidence: 98%